2020
DOI: 10.1002/hep4.1569
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy Validated Study of Biomarkers for Liver Fibrosis and Transplant Prediction in Inherited Cholestasis

Abstract: Alagille syndrome (ALGS) and progressive familial intrahepatic cholestasis (PFIC) are inherited cholestatic disorders with risk of developing end-stage liver disease requiring liver transplantation (LT). We investigated aspartate aminotransferase-to-platelet ratio index (APRI), Fibrosis-4 score (FIB-4), and conjugated bilirubin as biomarkers to assess fibrosis severity and risk for LT among children with ALGS and PFIC. This multicenter, cross-sectional study included 64 children with ALGS or PFIC (per genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(58 reference statements)
0
6
1
Order By: Relevance
“…Another important novel finding of our analysis is the missing impact of liver fibrosis on the outcome of partial biliary diversion and long-term SNL. In contrast to our expectations and previous reports 25 we could not demonstrate a worse outcome in patients with advanced fibrosis as compared with patients with lower-grade fibrosis. The risk of surgery and postoperative complications must be compared with the chance of avoiding transplantation with its lifelong consequences and/or the benefit of transplant-free years.…”
Section: Discussioncontrasting
confidence: 99%
“…Another important novel finding of our analysis is the missing impact of liver fibrosis on the outcome of partial biliary diversion and long-term SNL. In contrast to our expectations and previous reports 25 we could not demonstrate a worse outcome in patients with advanced fibrosis as compared with patients with lower-grade fibrosis. The risk of surgery and postoperative complications must be compared with the chance of avoiding transplantation with its lifelong consequences and/or the benefit of transplant-free years.…”
Section: Discussioncontrasting
confidence: 99%
“…Shiau et al showed recently (Hepatology Communications) that an increase in Fibrosis-4 score was associated with 1.36-fold higher odds for LT in PFIC patients. In addition, the aminotransferase-to-platelet ratio index or Fibrosis-4 score appear to associate with risk for future LT in children with PFIC [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the often postpartum onset of the disease or early manifestation of symptoms, suspected HCC should be taken into account regardless of its size and extent, but after exclusion of distant metastases. As these patients are often infants, histological confirmation should not be mandatory, but should be supplemented by elevated AFP values, high-grade suspected imaging and the determination of biomarkers [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Progression of PFIC can vary widely between individuals, 2 and several biomarkers have been reported as surrogate indicators of disease progression. 28 , 30 , 31 , 32 , 36 , 37 , 38 , 53 , 54 Notably, a decrease in SBA levels has been shown to correlate with reduction in pruritus severity. 55 In addition, elevated circulating values have also been linked with poor native liver survival in children.…”
Section: Introductionmentioning
confidence: 98%